Nano-hydroxyapatite accelerates vascular calcification via lysosome impairment and autophagy dysfunction in smooth muscle cells - Qi Liu (KeAi Communications Co., Ltd., 2022)
Vascular calcification (VC) is a common characteristic of aging, diabetes, chronic renal failure, and atherosclerosis. The basic component of VC is hydroxyapatite (HAp). Nano-sized HAp (nHAp) has been identified to play an essential role in the development of pathological calcification of vasculature. However, whether nHAp can induce calcification in vivo and the mechanism of nHAp in the progression of VC remains unclear. We discovered that nHAp existed both in vascular smooth muscle cells (VSMCs) and their extracellular matrix (ECM) in the calcified arteries from patients. Synthetic nHAp had similar morphological and chemical properties as natural nHAp recovered from calcified artery. nHAp stimulated osteogenic differentiation and accelerated mineralization of VSMCs in vitro. Synthetic nHAp could also directly induce VC in vivo. Mechanistically, nHAp was internalized into lysosome, which impaired lysosome vacuolar H+-ATPase for its acidification, therefore blocked autophagic flux in VSMCs. Lysosomal re-acidification by cyclic-3′,5′-adenosine monophosphate (cAMP) significantly enhanced autophagic degradation and attenuated nHAp-induced calcification. The accumulated autophagosomes and autolysosomes were converted into calcium-containing exosomes which were secreted into ECM and accelerated vascular calcium deposit. Inhibition of exosome release in VSMCs decreased calcium deposition. Altogether, our results demonstrated a repressive effect of nHAp on lysosomal acidification, which inhibited autophagic degradation and promoted a conversion of the accumulated autophagic vacuoles into exosomes that were loaded with undissolved nHAp, Ca2+, Pi and ALP. These exosomes bud off the plasma membrane, deposit within ECM, and form calcium nodules. Vascular calcification was thus accelerated by nHAP through blockage of autophagic flux in VSMCs.